Flipped learning in the English as a second language classroom: Bhutanese students’ perceptions and attitudes of flipped learning approach in learning grammar - Singay, S. (Indonesian Journal of Applied Linguistics, 2020)
Although extensive research has been carried out on the positive effects of flipped learning in a first language context, there remains a paucity of evidence on the impact of flipped learning in a second language context, specifically in Bhutan. The present study was undertaken to examine Bhutanese students’ attitudes and perceptions toward the flipped learning approach in a second language context. The participants of this study were forty students (20 females and 20 males). Data collection instruments used in this study were questionnaire and semi-structured interview. Findings from the questionnaire demonstrated that the flipped learning approach helped learners to learn grammar; moreover, the students showed positive attitudes and perceptions towards the flipped classroom approach. Similarly, findings from a semi-structured interview revealed four important themes of the flipped learning approach, which are: conducive learning atmosphere, use of more technology, better relationship, and collaboration.